Membangun Kompetensi Digital Siswa SMK di Bidang Akuntansi Menuju Era AI (pada SMK Al Fatah Banjarnegara) - Agung Nurmansyah; Lusi Yuliarti; Dianningsih Dianningsih (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The development of digital technology and artificial intelligence (AI) has brought major changes in the world of accounting, both in terms of work processes and the professional competencies needed. This Community Service activity aims to improve the digital competence of Vocational High School (SMK) students in the field of accounting, especially in understanding and adopting the role of technology and AI wisely. The activity was carried out in the form of an educational seminar at SMK Al Fatah Banjarnegara involving 100 students majoring in Accounting. The material includes the transformation of the accounting profession due to digitalization, the introduction of AI-based accounting software, and the importance of data literacy and critical thinking skills. The results of the activity showed an increase in students' understanding of the role of AI in accounting, as well as the formation of a mindset that AI is a tool, not a substitute for the human profession. This activity has a positive impact on fostering digital awareness, readiness to adapt, and student learning motivation. Potential future development includes practical training and replication of similar activities in other vocational schools. With the right approach, vocational school students can be prepared to become a superior and relevant vocational workforce in the era of digital transformation.